New Corporate Governance Successful Board Management Tools - Hilb, Martin (Management for Professionals, 2016)
In the 5th edition of this successful book Martin Hilb presents an innovative and integrated approach to the theory and practice of corporate governance. Central to this approach is a set of instruments - developed and tested by the author - that can be used by boards to offer effective strategic direction and control to their organizations. The board instruments can be readily applied to the selection, review, remuneration and development of board members, and for conducting board self-evaluations. This new approach to corporate governance is based on four guiding principles: keep it situational, keep it strategic, keep it integrated, and keep it controlled. Together, these principles form the basis of an integrated approach to all key aspects of corporate governance. The main arguments in each section are supported by conceptual models, practical board tools and case studies, making the book ideally suited to board members, senior managers and post-graduate students. This new edition is updated throughout the book and includes a new chapter on mobile integrated board management and documentation information systems. "Martin Hilb's new book will stimulate behavioral change behind board doors. Nothing is more important to the continuing improvement of board governance than the board self-appraisal tools promoted in this book". Professor David R. Beatty, Director of the 'Center for Board Effectiveness' of the University of Toronto "There is no 'one size fits all' corporate governance solution, but integrity is the basis for all, and above all common sense needs to be used. Hilb's new glocal approach illustrates this in an effective way". Noke Kiroyan, Chairman of the Board of Rio Tinto Corporation, Jarkarta "Martin Hilb's book is a welcome and substantial addition to the corporate governance debate. I have long respected and valued his insightful contributions to management issues. In this book he provides us with integrated and holistic concepts, and ways and means for achieving effective, real-world board management. With this book, responsible directors may well be encouraged to evaluate their own board performance. Therefore, it is essential reading for business leaders committed to successful corporate governance". Dr. Egon Zehnder, Chairman of the Board of Egon Zehnder International Inc, Zurich.